2015
DOI: 10.15376/biores.10.2.2020-2031
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Decomposition Properties of Materials from Different Parts of Corn Stalk

Abstract: aTo help better utilize corn stalk (CS), pyrolysis behavior of materials from different parts of the CS including corn stalk without pith, corn root, and corn leaf were analyzed using thermogravimetric analysis (TGA) at heating rates of 5, 10, 20, and 25 °C/min. The apparent activation energies determined by the Friedman method for corn stalk without pith, corn root, and corn leaf were in the range of 26.4 to 103.6 kJ/mol, 37.6 to 69.5 kJ/mol, and 35.0 to 103.9 kJ/mol, respectively, depending on the conversion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 21 publications
2
4
0
Order By: Relevance
“…These results are consistent with the data on different types of biomasses [43,47,49,52,53]. For lignin decomposition, there was no peak for any of the species studied, which may be because of its wide range of decomposition temperatures from 150 to 900°C without a sharp weight-loss peak [52][53][54]. Table 3 shows the devolatilization data of the wood of the invasive plants and A. tortilis, which were extracted from the curves of TGA and DTG according to Salaheldeen et al [49] and Chen and Kuo [52].…”
Section: Thermal Propertiessupporting
confidence: 88%
“…These results are consistent with the data on different types of biomasses [43,47,49,52,53]. For lignin decomposition, there was no peak for any of the species studied, which may be because of its wide range of decomposition temperatures from 150 to 900°C without a sharp weight-loss peak [52][53][54]. Table 3 shows the devolatilization data of the wood of the invasive plants and A. tortilis, which were extracted from the curves of TGA and DTG according to Salaheldeen et al [49] and Chen and Kuo [52].…”
Section: Thermal Propertiessupporting
confidence: 88%
“…These TGA findings are in agreement with sorghum 2 and corn stalk studies. 70 Previous studies have shown that the thermogravimetric (TG) curve varies with cellulose, hemicellulose, and lignin contents 68 and biomass type. 71 The residue char/ash left at 800 °C for D1, RG1, D2, and RG2 were, respectively, 22.5, 24.9, 16.6, and 19.9% (Table 2).…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 99%
“…In a first stage, the fastest weight loss can be attributed to the evaporation of the water existing in pores of the maize stalk. Cellulose, hemicellulose and lignin are major compounds of this plant material [27]. Second stages of weight loss between 200-400ºC range can be assigned to pyrolysis of hemicellulose.…”
Section: Thermal Characterization Of Maize Stalkmentioning
confidence: 99%